PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS CANVA BERBANTUAN MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN IPAS MATERI MAGNET, LISTRIK DAN TEKNOLOGI UNTUK KEHIDUPAN KELAS V SD - Azzahara Syahrilla; Hidayat, Hidayat (Jurnal Cakrawala Ilmiah, 2025)
This study aims to determine how the development and feasibility of learning media using the Canva application at SD Negeri 105300 Delitua. The research method used is research and development using the ADDIE model, namely A (analysis), D (design), D (development), I (implementation), and E (evaluation). The test subjects in this study were through a small-scale trial conducted at SD Negeri 105300 Delitua with 20 students as respondents. Product feasibility was carried out by 3 validation experts, namely 1 material expert validation, 1 media expert validation and 1 teacher. The results showed that the learning media using the Canva application was said to be feasible and very interesting. The feasible category was through the material expert validation score of 82.5%, the media expert validation score of 78% and the teacher assessment score of 79%. This result was also strengthened by students' opinions, which amounted to 87.6% with a very interesting category. Based on the results of this study, it is proven that learning media using the Canva application assisted by the problem-based learning model is highly recommended for use at SD Negeri 105300 Delitua because this learning media is very practical and innovative for students